Electronic Music, Sampling, and the Tape Snippet: How the Experimental Studio of Polish Radio Made Itself Useful. - Bohlman, Andrea F. (Contemporary Music Review, 2020)
Warsaw's Experimental Studio of Polish Radio (1957–2004) was integral to public media production in Poland. At the its consoles, composers and engineers studied acoustics, made incidental sounds for television, radio, and film, and composed large-scale works that circulated at new music festivals around the world during the Cold War. Their tape-oriented poetics, acoustic play, archival whimsy, and electronic production shaped the media imaginary of Polish science fiction, and provided soundtracks for radio plays and animated films for decades. Since its closure it has continued to generate creative projects that weave together an analogue electronic music past with the digital electronic music present. This article opens the doors to the Polish studio by following its central material, magnetic tape, through a range of contexts: the first composition realised at its consoles, a hip-hop history of the Polish twentieth century, as part of a cold-war gift economy among artist friends, and as the basis of a sample pack offered to users of the digital audio workstation Ableton Live. This material history reveals a range of uses for tape that urge us to revisit what it means for an arts institution under state socialism to frame its relationship to society as utilitarian.